2012
DOI: 10.1542/peds.2011-3788
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chronic Nonbacterial Osteomyelitis

Abstract: In a US cohort of 70 children with CNO, coexisting autoimmunity was a risk factor for multifocal involvement and treatment with immunosuppressive agents. Disease-modifying antirheumatic drugs and biologics were more likely to lead to clinical improvement than NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
219
4
30

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(259 citation statements)
references
References 47 publications
6
219
4
30
Order By: Relevance
“…In contrast, some studies have reported that only 13% of patients achieved clinical remission using NSAIDs (28). Thus, the outcome of our patients appears to be very favorable.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, some studies have reported that only 13% of patients achieved clinical remission using NSAIDs (28). Thus, the outcome of our patients appears to be very favorable.…”
Section: Discussioncontrasting
confidence: 60%
“…Метотрексат и сульфасалазин использовались при заболеваниях со схожим патогенезом, такими как анкилозирующий спондилоартрит, псориатический артрит, энтезитассо-циированный артрит, воспалительные заболевания кишечника, и могут быть использованы при нетяже-лых формах небактериального остеомиелита, особенно в случаях, ассоциированных с этими заболеваниями и, как правило, в комбинации с НПВП [7]. Сульфа салазин оказался эффективным у 66% детей [8].…”
Section: обоснованиеunclassified
“…Метотрексат эффективнее у пациентов с небактериальным остеоми-елитом с сопутствующим артритом. Наибольшая эффек-тивность метотрексата (у 91% детей) показана в много-центровом исследовании с участием трех крупнейших детских ревматологических центров США [8].…”
Section: обоснованиеunclassified
See 2 more Smart Citations